Social and cultural influences and their implications for sustainable tourism: A case study of Trinidad & Tobago's tourism and the growth of the LGBTQ traveler segment - Annette A. George (Goodwood Publishing, 2021)
Purpose: This study examined how social and cultural influences are affecting the government of Trinidad & Tobago's decision-making policies as it relates to the growth of the LGBTQ traveler tourism segment, which is currently threatening the sustainability and competitiveness of the country's tourism industry. This study also aimed to add to the literature on gay tourism in that nation and region as a whole. Research methodology: Data for this research were collected from various sources, including existing literature on the industry's competitiveness, followed by a review of official government surveys, reports and other media documents, and academic research literature. Results: The study's findings reveal that the leaders' lack of failure to understand the economic power of the LGBTQ traveler segment is short-sighted and has negative effects on the fragile nature of the industry's ability to compete globally, lack of long-term vision of the leaders. Limitations: This study relied on secondary data, limiting direct views from individuals in the local communities due to the country being on lockdown since March of 2020 as a result of the COVID-19 pandemic. Contribution: This study makes a few suggestions for further improvement, such as leaders in that nation deciphering existing buggery laws publicly, to show urgency and commitment to this vulnerable traveler segment; conducting robust discussions with various interest groups that are presenting barriers to changes that could result in a more robust industry, and finally, consider the use of images of members of the LGBTQ community in all marketing promotions.